Parental health literacy and health knowledge, behaviours and outcomes in children: a cross-sectional survey - Elke de Buhr; Antje Tannen (BMC Public Health, 2020)
Abstract Background Health literacy (HL) is closely associated with leading health indicators such as engaging in healthy behaviours and experiencing a healthy social environment. Parents represent a critical subgroup among the adult population since they are not only responsible for their own health but also for the health of their children. Previous research suggests that parents with low HL are less likely to meet the preventive and health care needs of their children but there are gaps in the available information and there is not any data available yet for the German context. Methods In preparation of an implementation study, a cross-sectional survey was conducted in 28 elementary and secondary schools in Germany. The parent questionnaire was completed by 4217 parents and included the short form of the European Health Literacy Survey Questionnaire (HLS-EU-Q16). The child questionnaire examined children’s health knowledge, behaviours and outcomes. For children between 6 and 10 years, a parent reported on behalf of their children (N = 1518). Students 11 years and older completed a self-administered questionnaire (N = 2776). Bivariate and multivariate analyses were carried out. Spearman’s Rho correlations assess the relationships between household characteristics, parental HL and the health behaviour and outcomes in children. Results Among the participating parents, 45.8% showed problematic or inadequate HL. The major determinants of high parental HL were high socio-economic status (SES) (r = .088***, 95% CI [.052, .124]), living in West Germany (r = .064***, 95% CI [.032, .096]) and older parental age (r = .057**, 95% CI [.024, .090]). In the multivariate model, only SES remained significant. High parental HL was associated with positive health behaviours in children including healthier nutrition, regular tooth brushing and more physical activity. The relationships between parental HL and smoking, alcohol, sexual activity among children and children’s weight were not significant. Conclusions The results confirm a relationship between low parental HL, SES and some child health behaviours likely to negatively impact their health and wellbeing including less healthy nutrition and less exercise. Strengthening the health knowledge and competencies of parents may contribute to improved child outcomes particularly in the areas of nutrition, exercise and dental health.